REPRODUCTIVE ASPECTS OF SCALLOPED PERCHLET, Ambassis nalua (HAMILTON, 1822) IN PABEAN BAY INDRAMAYU, WEST JAVA - Nisha Desfi Arianti; M.F. Rahardjo; Ahmad Zahid (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
ABSTRACTScalloped perchlet, Ambassis nalua,  is one of fishes in Pabean Bay, Indramayu. This research aims to determine the reproductive aspects of Ambassis nalua in Pabean Bay Indramayu including sex ratio, spawning season, first maturity, fecundity and spawning pattern. Fish samples were collected by trap net and trammel net at three sites in Pabean Bay from April to October 2015. A total of 424 of A. nalua were caught, consist of 114 males and 310 females; with total length ranged from 38.04 to 112.63 mm and total weight ranged from 0.37 to 25.44 g. Sex ratio of mature fish  was 1:1.9. The mature males and females were found in every month of sampling period. The gonado-somatic index (GSI) ranged from 0.40 to 0.83 and 2.36 to 4.54 for male and female, respectively. The peak of spawning season was found in September. The first maturity (Lm50) for male and female were 79.17 mm and 91.25 mm, respectively. The fecundity varied from 3,451–32,465 eggs. Egg diameter distribution shows that spawning pattern of A. nalua was batch spawner. Keywords: Ambassis nalua, spawning season, sex ratio, reproduction